Anti-cholinergics mecamylamine and scopolamine alleviate motion sickness-induced gastrointestinal symptoms through both peripheral and central actions. (1st March 2019) - Qi, Ruirui; Su, Yang; Pan, Leilei; Mao, Yuqi; Liang, Lu; Dai, Zhiqiang; Wang, Junqin; Cai, Yiling
Abstract: Enhanced cholinergic activity contributes to the production of complex autonomic manifestations of motion sickness (MS). However, whether anti-cholinergics exert their anti-MS effects through central or peripheral actions remained unclarified. In the present study, we investigated the effects of mecamylamine (MEC) and scopolamine (SCOP) on rotation-induced gastrointestinal symptoms (conditioned gaping and defecation), locomotion disturbances (hypoactivity and impaired balance performance), hypothermia as well as Fos expression in vestibulo-autonomic regions in rats. We also observed the effects of hexamethonium (HEX) and methyl scopolamine (MSCP) on those MS behavioral responses. The efficacy of all these drugs on rotation-induced emesis and other MS symptoms in cats was also examined. We found that intragastric administration of MEC and SCOP inhibited rotation-induced gaping and defecation in rats, but only MEC showed a dose-dependent manner. MEC aggravated rotation-induced balance disorder and failed to attenuate rotation-induced hypothermia as the SCOP did. MEC was more effective for inhibiting Fos expression in the caudal vestibular nucleus and nucleus of solitary tract than SCOP. Intraperitoneal injection of HEX and MSCP also significantly alleviated rotation-induced gastrointestinal symptoms, and showed benefit to balance performance in rats. In cats, MEC, SCOP and HEX had prophylactic effects against rotation-induced emesis and salivation, and deceased non-retching/vomiting symptoms, but MSCP only attenuated emesis. It suggested that MEC and SCOP might alleviate gastrointestinal symptoms of MS via inhibiting peripheral autonomic nervous system and central vestibulo-autonomic pathways. The nicotinic acetylcholine receptor inhibitors like MEC might be new candidates against gastrointestinal symptoms induced by MS or other vestibular disorders. Highlights: MEC and SCOP as well as HEX and MSCP alleviated MS-related nausea and emesis. MEC failed to attenuate MS-related hypothermia as the SCOP did, but aggravated MS-induced balance disorder. MEC was more effective for inhibiting Fos expression in the CVN and NTS than SCOP.